Guidelines for clinical research nurses about their self-leadership role in nursing practice at nursing units in the southern suburbs of Cape Town, Western Cape - Reddy, Cordelia Kruparakshnam (University of the Western Cape, 2016)
Magister Curationis - MCur === Clinical research nurses are at the frontline of clinical research. They act as nurse leaders in the area of patient-orientated research. This leadership role requires that they work independently with limited support from other nurses. The nursing practice of clinical research nurses’ associates patient care with research protocols, administration duties, management responsibilities, and role specific authority. At hospitals in the Western Cape, clinical research nurses support principal investigators in the conducting of clinical research. It was unclear how clinical research nurses in nursing units in southern suburbs, Cape Town, Western Cape Province experienced their self-leadership role in nursing practice. The aim of the study was to explore and describe the experiences of clinical research nurses’ self- leadership role in nursing practice in nursing units in the southern suburbs of Cape Town, Western Cape. In this study; a phenomenological, exploratory, descriptive, and contextual design was followed. The population consisted of all the clinical research nurses (n = 22) at Western Cape hospitals and health care institutions in the southern suburbs. Purposive sampling was applied according to selection criteria. Unstructured individual interviews were conducted until data saturation occurred. These interviews took place at a private office in the southern suburbs of the Cape Town and lasted between 45 minutes and an hour. Observation and field notes were taken during the interviews. Data was analysed by using open coding and data triangulation. The researcher applied Lincoln and Guba’s (1985) model of trustworthiness. Four themes and twenty one categories emerged from the data analysis. The findings emphasised that the clinical research nurses’ experienced their self-leadership role in nursing as an evolutionary process. The evolutionary role required that they needed to develop strategies with the aim of surviving the initial tedious and daunting phase that facilitated the development of skills needed for collaborative partnerships with stakeholders. As her general confidence increased, the clinical research nurse would be able to recognise her professional attributes and use self-leadership behaviour to enhance her daily practice. Appropriate self-leadership behaviour would assist the clinical research nurse to successfully navigate the complex, dynamic clinical research environment. Guidelines were developed from the four themes that were the result of the data analysis; namely the initial tedious and daunting phase, working in pursuit of collaborative action, personal traits of the clinical research nurse, and self-leadership behaviour. The UWC Higher Degree Committee at the Faculty of Community and Health Sciences and the Senate Research Committee respectively approved this research project. No risks were anticipated for participants in the study.